New records of seaweeds from southeastern coasts of Cox’s Bazar district, Bangladesh - Aziz, Abdul; Alfasane, Md Almujaddade (Bangladesh Journal of Plant Taxonomy, 2020)
Gracilaria tenuistipitata var. liui Zhang et Xia from sand-flat at Nuniachara, Cox’s Bazar, Ulva linza Linnaeus from west coast of Naf River at Noapara, Teknaf and Fishary Ghat in the River Bakkhali, at Cox’s Bazar and Caulerpa fergusonii G. Murray from St. Martin’s Island (SMI) have been newly recorded and illustrated from Bangladesh. Caulerpa chemnitzia (Esper) J.V. Lamouroux var. irregulare Aziz & Alfasane var. nov. and C. sertularioides (S.G. Gmelin) M. Howe var. robusta Aziz & Alfasane var. nov. from SMI, Cox’s Bazar District, Bangladesh are new to science. Total number of marine algal taxa recorded from Bangladesh coasts till 2020 is 210. Bangladesh J. Plant Taxon. 27(2): 335-343, 2020 (December)